The Engine Mechanical Coordinates Measuring in the Asynchronous Motor - Dementyev Yuriy N.; Umurzakova Anara D. (MATEC Web of Conferences, 2014)
The article considers indirect control devices for the mechanical coordinate’s measurement of a three-phase asynchronous electric motor, which detects the temperature of the stator winding conductors and the basic frequency of stator voltage. Characteristics of mechanical coordinate’s simulation of the asynchronous motor are provided to assess the accuracy of the mechanical coordinate’s measurement in the dynamic modes.